THE UTILIZATION OF E-LEARNING MEDIA ASSISTED BY GOOGLE CLASSROOM AND GOOGLE MEET IN LEARNING TEST OF ENGLISH AS A FOREIGN LANGUAGE (TOEFL) PREPARATION DURING THE PANDEMIC - Maria Safriyanti (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The purpose of writing this article was to describe narratively how the implementation of TOEFL Preparation learning process for 2020’s new students who took online learning such as the use one of e-learning platform like google classroom and google meet during the Covid-19 pandemic. The learning method used was in the form of giving assignments through google classroom and direct learning practice with google meet based on the given assignments. The learning results showed the enthusiasm of students in participating in this learning activity. This was evidenced by the fact that almost students attended this online learning. However, there are obstacles faced, namely the lack of good network at certain times so that there was a student's lack of understanding of the material presented. However, from the results of direct observation during the implementation of learning, it can be said that the use of e-learning, especially in the use of google classroom and google meet, are able to help students to continue and to participate in distance learning.